Plurilingualism in Traditional Eurasian Scholarship Thinking in Many Tongues - Most, Glenn W.; Schäfer, Dagmar; Saarela, Mårten Söderblom (Brill, 2023)
Was plurilingualism the exception or the norm in traditional Eurasian scholarship? This volume presents a selection of primary sources-in many cases translated into English for the first time-with introductions that provide fascinating historical materials for challenging notions of the ways in which traditional Eurasian scholars dealt with plurilingualism and monolingualism. Comparative in approach, global in scope, and historical in orientation, it engages with the growing discussion of plurilingualism and focuses on fundamental scholarly practices in various premodern and early modern societies-Chinese, Indian, Mesopotamian, Jewish, Islamic, Ancient Greek, and Roman-asking how these were conceived by the agents themselves. The volume will be an indispensable resource for courses on these subjects and on the history of scholarship and reflection on language throughout the world.